A Prospective Study of the Role of Inflammation in Bladder Cancer - Qayyum, Tahir (S. Karger AG, 2013)
INTRODUCTION: To examine the role of inflammation in bladder cancer, we assessed the relationship between a systemic inflammation prognostic score (modified Glasgow Prognostic Score, mGPS), the tumor inflammatory cell infiltrate as measured by the Klintrup-Makinen score and tumor necrosis with cancer specific survival in patients with bladder cancer. MATERIALS AND METHODS: The cohort consisted of 68 bladder cancer patients, 47 with localised disease and 21 with muscle invasive disease. The mGPS response was constructed by measuring C-reactive protein and albumin concentrations and the Klintrup-Makinen score was evaluated histologically for the local inflammatory response. Pathological parameters such as grade, T stage and tumor necrosis were also assessed. RESULTS: Median follow was 47 months and 24 patients died of their disease. On univariate analysis, T stage (p < 0.001), grade (p < 0.001) and mGPS (p = 0.002) were significant predictors of cancer specific survival. On multivariate analysis, T stage (hazard ratio 5.98, 95% confidence interval 3.18–11.24, p < 0.001) and mGPS (hazard ratio 1.78, 95% confidence interval 1.09–2.9, p = 0.02) were significant independent predictors of cancer specific survival. CONCLUSION: A preoperative systemic inflammatory response is an independent predictor of poor cancer specific survival in patients with bladder cancer.